Spatial analysis of under five years pneumonia incidence in DIY Province 2020 - Kusumadewi, Ni Nengah Sri; Makful, Martya Rahmaniati; Meutia, Liza (Universitas Gadjah Mada, 2023)
Purpose: Globally, pneumonia is a major cause of morbidity and mortality, as the largest burden of disease and death in developing countries. In 2018, more than 19,000 children under five died from pneumonia. The Under-five Mortality Rate (AKBa) reflects the social, economic, and environmental conditions in which children live and maintain their health. WHO issued an integrated global action to prevent and control the incidence of pneumonia and diarrhea (GAPPD). Yogyakarta is in the second position with the highest prevalence of pneumonia under five (3.7%). To carry out a more focused pneumonia prevention program, spatial pattern analysis is needed both globally and locally, this study examines whether there is a global and local spatial correlation in the number of pneumonia cases under five years in Daerah Istimewa Yogyakarta (DIY) in 2020. Methods: This ecological study uses aggregated data at the sub-district level. DIY Province has 78 sub-districts that serve as the unit of analysis. Results: The global spatial autocorrelation test on the number of cases of toddler pneumonia in DIY is significantly positive. High-high areas include the sub-districts of Semin, Ponjong, Rongkop, Semanu, Karangmojo, Wonosari, Playen, Paliyan, Saptosari and Panggang. Hot spots were found in the southeastern region. A closer look at the sub-districts in the hotspot area, all from Gunung Kidul Regency, shows that specific interventions targeting these areas must be strengthened, regional health planning and resource allocation. Conclusion: A cluster correlation (clustering) exists spatially with the number of toddler pneumonia in the DIY. Locally, it can be seen that the hot spots (high-high) and low-high districts are found in one district. So it is a priority area that needs comprehensive handling but with a different emphasis according to the characteristics of each sub-district in one district.